Loneliness, Social Isolation, and All-Cause Mortality in a Large Sample of Older Adults. (October 2022) - Barnes, Timothy L.; Ahuja, Manik; MacLeod, Stephanie; Tkatch, Rifky; Albright, Laurie; Schaeffer, James A.; Yeh, Charlotte S.
Objectives: Using data from a large random sample of U.S. older adults ( N = 7982), the effect of loneliness and social isolation on all-cause mortality was examined considering their separate and combined effects. Methods: The UCLA-3 Loneliness Scale and the Social Network Index (SNI) were used to define loneliness and social isolation. Cox proportional hazards regression models were performed. Results: Among study participants, there were 548 deaths. In separate, adjusted models, loneliness (severe and moderate) and social isolation (limited and moderate social network) were both associated with all-cause mortality. When modeled together, social isolation (limited and moderate social network) along with severe loneliness remained significantly associated with mortality. Discussion: Results demonstrate that both loneliness and social isolation contribute to greater risk of mortality within our population of older adults. As the COVID-19 pandemic continues, loneliness and social isolation should be targeted safely in efforts to reduce mortality risk among older adults.